Demand Modeling with Overlapping Time Periods. (2015) - Kadric, Edin; Bajric, Hadis; Pasic, Mugdim
Abstract: It is common and also predominant in the inventory control literature that demand follows normal distribution, and according to central limit theorem, demand per period will also follow normal distribution. However, in many real life situations, demand does not necessary follow normal distribution, and therefore, use of expressions used to calculate demand parameters per period are not suitable. This research suggests that available demand data are grouped into periods of desired length by overlapping. Demand data obtained by this approach provide valuable information for risk study. Suggested approach is evaluated using periodic review inventory model where all unsatisfied demand is backordered, and the same inventory control model is used to control inventories of slow and fast moving items.